Análise dos fatores que ajudam a explicar as diferentes performances de exportação do complexo soja no Brasil e na Argentina no período entre 1990 e 2019 - Gabbi, Maiara Thaís Tolfo (2019)
In the last decades, Argentina has been distinguished by the increase in soybean meal and oil exports, while Brazil by the increase in soybean grain exports, which shows antagonistic export trajectories. This dissertation aims to analyze the performance of Soy Complex exports in Argentina and Brazil from 1990 to 2018 and to investigate which factors explain the intensification of bran and oil exports by Argentina, and grain exports by Brazil. The theoretical framework used contemplated the theories of economic regulation, industrial policy and trade policy and the comparative advantages revealed. The procedures employed to meet the research objectives include the collection of primary data through semi-structured interviews explored by content analysis and secondary data collection treated by the Market Share (MS) and Herfindahl-Hirschman Index (IHH) indicators and by linear regression. . The results show that the soybean processing segment in Argentina has mainly comparative advantages derived from the concentration of production, which takes place within a radius of approximately 300 km, located close to the crushing industries, industrial plants with high processing capacities (20 thousand tons per day) and logistics facilitated by river and sea transport, resulting in scale gains and cost reductions. In addition, a tax differential, with lower export duties for domestic processing and thus representing an incentive to crush, instrumental policies that structured the development of logistics infrastructure and the waterway within this range of soybean grain production and processing, Argentina was structured to export soybean meal. Restricted domestic demand from the neighboring country is also a stimulus for the export of bran and oil, as well as the issues associated with collecting royalties for using Monsanto's RR technology, which has led Argentine processing industries to prioritize exports of bran and oil, given the legal enforceability of royalty collection in the European Union over a given period. On the other hand, the soy complex in Brazil intensified grain exports, mainly due to Chinese demand for grains, the imposition of trade barriers by China on imports of derivatives and the tax incentives derived from the Kandir Law. In addition, the large distances between production centers and ports in Brazil, together with infrastructure and logistics constraints, are limiting the competitiveness of soybean meal and oil exports. Logistics operators in Ports do Brasil are also less willing to operate bran and oil cargoes, since soybeans have greater liquidity and easier cargo operations. Other factors that may influence soybean trade in Brazil and Argentina were also verified, among them, the possible medium and long term impact exerted by the changes of power of the industry to the ruralist bank in Argentina, the concern with the quality standards required in soybean meal production for both countries, and the need and pursuit of future negotiations with China to expand domestic processing. Finally, the interviews allowed us to analyze the export scenario of Brazil and Argentina and conclude that Brazil's biggest challenge will be to overcome the obstacles exerted by the great distances, the lack of investments in infrastructure and logistics and the need for trade negotiations to expand exports of products with higher added value.